The big book of reproducible graphic organizers - Jacobson, Jennifer; Raymer, Dottie (New York : Scholastic Professional Books, 1999)
Presents a collection of fifty reproducible graphic organizers--visual representations that may be used to help students develop thinking strategies--covering language arts, social studies, science, mathematics, and study skills, each with directions for its use.
"50 great templates to help kids get more out of reading, writing, social studies & more."
"All grades"-Cover.
Professional.
Professional
Keywords: Creative activities and seat work; Teaching -- Aids and devices; Creative activities; Teaching -- Aids and devices